TNFα-mediated liver destruction by Kupffer cells and Ly6Chi monocytes during Entamoeba histolytica infection. - Elena Helk; Hannah Bernin; Thomas Ernst; Harald Ittrich; Thomas Jacobs; Joerg Heeren; Frank Tacke; Egbert Tannich; Hannelore Lotter (PLoS Pathogens)
Amebic liver abscess (ALA) is a focal destruction of liver tissue due to infection by the protozoan parasite Entamoeba histolytica (E. histolytica). Host tissue damage is attributed mainly to parasite pathogenicity factors, but massive early accumulation of mononuclear cells, including neutrophils, inflammatory monocytes and macrophages, at the site of infection raises the question of whether these cells also contribute to tissue damage. Using highly selective depletion strategies and cell-specific knockout mice, the relative contribution of innate immune cell populations to liver destruction during amebic infection was investigated. Neutrophils were not required for amebic infection nor did they appear to be substantially involved in tissue damage. In contrast, Kupffer cells and inflammatory monocytes contributed substantially to liver destruction during ALA, and tissue damage was mediated primarily by TNFα. These data indicate that besides direct antiparasitic drugs, modulating innate immune responses may potentially be beneficial in limiting ALA pathogenesis.